(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Music archeologically, the uniqueness of the jew’s harp is that, when studying an excavated object, it can be almost definitely determined that it is nothing other than the jew’s harp when it meets certain criteria. The author discusses the similarities between the four examples of the bow-shaped iron jew’s harp from Saitama and Chiba Prefectures, Japan (9-10th Century AD) and their chronological counterparts from Primorsky Krai, Russia and Heilongjiang Province, China – the area across the Sea of Japan, from where Mohe, Balhae and Jurchen jew’s harps were unearthed. Also, he supposes how the jew’s harp could reach to Japan, referring especially to the ancient cultural exchanges through Balhae missions to Japan dispatched thirty-four times between 727 and 919.